Kerusakan Dokumen Rekam Medis di Ruang Penyimpanan (Filling) Rumah Sakit Nur Hidayah Bantul Tahun 2019 - Ika Oktaviyani (International Journal of Healthcare Research, 2019)
Storage space as a place to store, retrieve and return medical records for outpatients, inpatients and emergency services, and protect medical records from theft, physical, chemical, and biological damage. The damage to medical record documents in the storage room of Nur Hidayah Hospital in 2018 were 50 medical records, of the 50 medical records, 20 medical records could still be used and the rest could not be used, 30 medical records were eaten by termite insects, torn folders as many as ± 50 medical records, and untidy arrangement. The condition of the storage room was damp and narrow so that the hospital experienced the impact of difficulty in finding patient history. This type of research is a qualitative descriptive study with a case study research design. Data collection was carried out by interview and observation. The data analysis was conducted in a descriptive qualitative manner. Ensuring the validity of the data in this study used source triangulation and method triangulation. The results showed that the damage to medical records in the storage room, the physical factors of the narrow and less spacious room conditions, some of the shelves are still made of wood, no temperature and humidity gauges, abnormal temperature and humidity, leaky roofs, and no campgrounds. , biological factors were found to be fungi, and human negligence factors were found by officers to take and compile unorganized medical records. The impact of damage to medical records is a lot of lost, unreadable patient data, difficulty in finding medical records, long services, and untidy storage. Damage to medical records in the storage room of Nur Hidayah Hospital is caused by physical, biological, and human negligence.